Super Genes: The hidden key to total well-being - Deepak Chopra and Rudolph E. Tanzi
"You are not simply the sum output of your genome," write Deepak Chopra and Rudy Tanzi, Director of the Genetics and Aging Research Unit at Massachusetts General Hospital. "You are the user and inventor of your genome." For years it was accepted knowledge that genes were fixed components of our bodies, and that we as individuals were incapable of altering our genetic make-up. Yet groundbreaking research suggests that changes in lifestyle and diet can greatly influence our genetic predispositions to disease and certain physical and psychological behaviours. Moreover, the adoption of ancient Vedic practices such as yoga and meditation can create genetic mutations that allow us to lead longer and healthier lives. Super Genes includes meditation and breathing practical exercises, as well as information on how to manage risk factors for disease. Combining scientific research with insights from ancient traditions, Chopra and Tanzi show how we need not be at the mercy of our genetic inheritance. Instead, they argue, we have the power to rewire our super genes for health and happiness.